تأثير التسويق الالكتروني على تحسين جودة الخدمة: بالبنوك التجارية الكويتية - المطيرى، عبدالعزيز مجعد فارع; عطية، طاهر مرسي Attiah, Taher Mursi; جودة، سماح محمد محمد Jawdah, Samah Mohammed Mohammed (جامعة بورسعيد - كلية التجارة, 2020)
The research aims to analyze the relationship between e-marketing and improving the quality of services, while trying to present some appropriate results and recommendations to help officials in implementing e-marketing, through a sample of commercial bank workers in the State of Kuwait, which was estimated at (384) single. The research found a statistical relationship between e-marketing and improving the quality of services. The research also suggested several recommendations, including seeking to develop electronic marketing methods and developing Internet programs, with training plans linked to e-marketing results in banks.
يهدف البحث إلى تحليل العلاقة بين التسويق الإلكتروني وتحسين جودة الخدمات، مع محاولة تقديم بعض النتائج والتوصيات المناسبة لمساعدة المسئولين في تطبيق التسويق الإلكتروني، من خلال عينة من العاملين البنوك التجارية بدولة الكويت التي قدرت ب(384) مفردة. وتم التوصل إلى العلاقة إحصائية بين التسويق الإلكتروني وتحسين جودة الخدمات، كما اقترح البحث عدة توصيات ومنها السعي إلى تطوير وسائل التسويق الإلكترونية وتطوير برامج الإنترنت، مع ربط الخطط التدريبية بنتائج التسويق الإلكتروني بالبنوك.
Keywords: التسويق الإلكترونى -- البنوك التجارية -- الأوراق المالية -- الكويت